Aplicación de los códigos QR en el control de bodegas - Ovares-Mora, José David (Instituto Tecnológico de Costa Rica, 2016)
6 The project will involve the implementation of the QR code in the construction industry by applying it to the administration and control of wine. The QR code (quick response code, for its acronym in English, quick response code, it would be if Spanish translation). It is useful for storing information in an array of points or a two-dimensional bar code created in 1994 by the Japanese company Denso Wave, a subsidiary of Toyota module. It is characterized by the three squares that are in the corners (as shown in figure 5) and that allow to detect the position of the code to the reader. The creators (a team of two people in Denso Wave, led by Masahiro Hara) aimed that the code would allow its contents to be read at high speed. While initially used to record area parts in vehicle manufacturing, QR codes today are used for inventory management in a variety of industries. Under this premise it is to develop this graduation project.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2016.
Keywords: QR code; Administración; Bodegas; Materiales; App Inventor